Pengaruh Kaca Penutup Double Slope dengan Piramida Menggunakan Pelat Penyerap Sirip terhadap Kinerja Solar Still - Ridwan, Mohammad; Ismail, Nova Risdiyanto; Hermawan, Dadang; Suwandono, Purbo (Universitas Nusantara PGRI Kediri, 2023)
Solar desalination technology is a technology that utilizes sunlight as the main energy resource to produce clean water through the process of heating seawater. This study compared solar stills using a double slope cover glass model with a pyramid model. The study used an experimental method to compare the cover glass of the double slope model and the pyramid model. The data taken are temperature, solar radiation intensity and water productivity. The thickness of the water above the basin is 1 cm. The study resulted in the highest productivity and efficiency of solar stills using the highest double slope model cover glass of 2,780 liters and an efficiency of 37.79% compared to solar stills using pyramid model cover glass with a productivity of 2,580 liters and an efficiency of 35.16%.